A Memo on Factors Associated with Perception of Stigma Attached to PrEP: Evidence from the Keeping It LITE Study - Shahin Davoudpour; Gregory L. Phillips II; Pedro A. Serrano; Audrey L. French; Sybil G. Hosek (Sexes)
Although perception of stigma (PS) has been dubbed as a key barrier to the optimal uptake of PrEP, research on PS is sparse. More specifically, no scholarly work has explored factors associated with the expression of PS toward PrEP use. This study addresses the literature gap by investigating factors associated with PS toward PrEP use. Data were drawn from the baseline survey (2017–2019) of the “Keeping It LITE Study”, involving a large cohort (n = 3330) of young sexual minority men, transgender men and women, and non-binary individuals in the US. Participants’ ages ranged from 13 to 34 years, with the majority (87%) assigned male at birth. The racial composition of the sample was diverse, with 53.9% identifying as white, 19.8% as Latinx, 10.7% as Black or African American, and smaller proportions as Asian, American Indian or Alaska Native, Native Hawaiian or other Pacific Islander, and another race/ethnicity. Logistic regression models were utilized to examine two common measures of PS in PrEP use: (1) the perception that PrEP users are seen as promiscuous and (2) the perception that PrEP users are assumed to be HIV-positive. Two sets of models were developed to account for the correlation between gender identity and sex assigned at birth. The results suggest strong PS among current PrEP users, which can explain the weak PrEP adherence reported among this group. The findings underscore the need for targeted interventions to mitigate PS and enhance PrEP uptake and adherence in vulnerable populations. Social and practical implications of the results and directions for future research are discussed.